Efeitos do exercício aeróbio de baixa intensidade e de longa duração no músculo psoas de camundongos mdx: modelo experimental da Distrofia Muscular de Duchenne - Sigoli, Emilly (Universidade Federal de São Carlos, 2021)
Duchenne Muscular Dystrophy (DMD) is a hereditary muscle disease caused by a mutation in the X chromosome, characterized by the absence of dystrophin protein. This deficiency causes instability and loss of sarcolemma integrity, causing recurrent lesions in muscle fibers and loss of function. As time passes, fibers lose their ability to regenerate, which can be related to the depletion of satellite cells (SC). SC are essential in muscle regeneration processes. In response to stimuli such as growth or trauma, quiescent SC are activated, proliferate and differentiate into myoblasts so that the damage caused can be repaired. SC express myogenic markers that make it possible to identify them in the different phases of tissue repair. Objectives:Evaluation of the effects of low-intensity aerobic exercise on the population of satellite cells, on the distribution and trophism of different types of fibers and on the expression of PGC-1α of the psoas muscle of mdx mice, after 37 training sessions.Results: The morphological aspects of the mdx animals indicated significant changes such as variation in the size of the fibers, nuclear centralization, necrosis, among others. In the quantitative analysis, it was possible to observe a reduction in the number of SC and in the expression of PGC-1α in the psoas muscles of the mdx animals. On the other hand, after a long period of training, it was observed an improvement in the cytoarchitecture of the fibers, an increase in the proportion of quiescent satellite cells/activation, an increase in PGC-1α expression and an increase in the diameter in trained dystrophic mice (MDX-TR) when compared to sedentary dystrophic ones (MDX-SED). Conclusion: Low-intensity aerobic training over a long period seems to be able to improve the cytoarchitecture and increase the activation of satellite cells in the psoas muscle of mdx mice, as well as activate signaling pathways that promote an increase in oxidative metabolism, which represents a viable therapeutic route for the treatment of DMD.
Effects of low-intensity and long-term aerobic exercise on the psoas muscle of mdx mice: an experimental model of Duchenne Muscular Dystrophy
Keywords: Distrofia Muscular de Duchenne; Camundongos mdx; Células satélites; Exercício aeróbio de baixa intensidade; Imunofluorescência; Duchenne Muscular Dystrophy; mdx Mice; Satellite cells; Low-intensity aerobic exercise; Immunofluorescence; CIENCIAS BIOLOGICAS::FISIOLOGIA